(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Accurate sexing of skeletal remains is a vital part of any medicolegal investigation and a challenge to physical anthropologists. Hip bone is considered as the most reliable sex indicator in the human skeleton. Standards of morphometric sex difference in the skeleton may differ with the population. The ability to determine sex from unknown skeletal remains is important. The hip bone is considered as an ideal bone for sex determination as it provides the highest accuracy. The human skeletal remnants have been researched extensively in forensic anthropology for medico-legal significance (1). Coxal index, Ischio-pubic index and the width of greater sciatic notch are the reliable parameters for sex determination of hip bone. Therefore the study of sexual dimorphism of bones in human population is of interest not only for the anatomist but also forensic experts and anthropologists.(2) AIM : To determine the sex of the individual from the hip bone using Coxal index, Ischio pubic index and the width of the greater sciatic notch,. MATERIALS & METHODS : Dry human disarticulated hip bones were collected in the Department of Anatomy Meenakshi medical college and research institute. For the study 75 human dry Hip Bones(36 male and 39 female) of known sex were taken. Adult Dry hip bones which were ossified having no deformities and congenital anomalies were taken for the study. The Coxal index, Ischio pubic index and the width of the greater sciatic notch were calculated. The mean and standard deviation were calculated for its significance. RESULTS: The mean value of Coxal index of male hip bone was 69.65± 5.1 and in female 71.8±4.7 the sex differences in the mean value of female is more than male and it is significant. Similarly, the Ischio pubic index and the width of greater sciatic notch are significantly higher in female than male. CONCLUSION: Hip bone is considered as the ideal bone for identification of sex next to the skull. Many parameters have been reviewed and found useful for the sex determination from the hip bone. Many studies emphasized the importance of the metric parameters of the hip bone. Our study specifically highlighted the determination of the sex from the hip bone using Coxal index, Ischiopubic index and width of the greater sciatic notch in Indian population.